Peritonitis in Children on Chronic Peritoneal Dialysis: The Experience of a Large National Pediatric Cohort - Ponce, Daniela [UNESP]; De Moraes, Thyago Proença; Pecoits-Filho, Roberto; Figueiredo, Ana Elizabeth; Barretti, Pasqual [UNESP] (Karger Publishers, 2018)
Background: We performed this study to evaluate the incidence, risk factors, microbiology, treatment, and outcome of peritonitis in pediatric Peritoneal dialysis (PD) patients at a nationwide prospective study. Methodology: Patients younger than 18 years recruited in the BRAZPD II study from 2004 to 2011, who presented their first peritonitis episode, were included in the study. Results: We found 125 first episodes of peritonitis in 491 children PD patients (0.43 episodes/patient-year). Patients free of peritonitis episode constituted 75.6% in 1 year. Culture-negative episodes were very high (59.2%) and gram-positive (GP) bacteria were the most commonly found organisms (58.8%). First-generation cephalosporin was the initial choice to cover GP (40.5%) and aminoglycosides was the most prescribed antibiotics used for gram-negative agents (27.5%). Treatment failure was 26.4%. Technique failure (TF) occurred in 12.1% and peritonitis was the main cause (65.1%). Pseudomonas (p = 0.04) and negative cultures (p < 0.001) were identified as predictors of TF. Conclusion: Peritonitis remains a common complication of PD in children and negative cultures and pseudomonas had a negative impact on TF.
Keywords: Children; Peritoneal dialysis; Peritonitis and outcome